Automatic Sand Sieving Machine with Three Sieves - Nofriady Handra; David A.; Randa J (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2016)
Sand is the base ingredient in the development process. In addition, the material cannot be separated sand use in the industrial world. Often in industrial buildings and workers needed sand material that has been processed. Sand material is usually still mixed with rocks or gravel. To get fine sand material, do the sifting process. The sieving process is carried out in order to get ready for the sand used in the process. The design of this sand sifter tools will provide convenience and a better process when compared with the work done traditionally. Benefits of making the application of automatic sand sieving machine can help the construction workers, especially in the process of building the sand processing to several functionality and usability. And can be used to produce maximum results in conditions that are not limited in the field. The purpose of making sand sifter tools this automated system is to ease the work in process and streamline the shifting sands of time, economic and workforce. The process of making this tool consists of four main processes, manufacture sifter, frame and hopper manufacture, manufacture of other supporting components, and assembly of all components. From the results of tests and experiments, that for 20 kg of the starting material that contains sand and stone (gravel) is processed only takes approximately 25 seconds to produce three types of the filter sand and stone as well. In general, the innovation of this tool enabled us to increase production of larger sieve in a short time, for development work on a large scale; this tool is suitable for generating a large amount of production that would be more economical in terms of time and cost.